A RESEARCH BASED TRAINING OF SCIENTIFIC PAPER FOR TEACHERS - Rahmat, Nur; Lian, Bukman; Kristiawan, Muhammad
This research starts from the results of a preliminary study that the teachers as professionals having roles and functions in achieving the vision of the national education. One form of professional development of teachers is to write a scientific paper. The purpose of this research is producing a training module on writing scientific papers for teachers which valid, practical and effective. This research used Research and Development (R&D). The development model used was TIER (Training Intervention Effectivenes Research). The subjects in this study were eight teachers in the SD Negeri 1 Rejosari and nine teachers in SD Negeri 3 Rejosari. The results of this research concluded that the teachers were able to write a scientific paper and publish it. The conclusion in this study showed the module was valid, practical and effective.